Update on overview of ocular manifestations of COVID-19 - Akbari, Mitra; Dourandeesh, Maryam (Frontiers in Medicine, 2022)
The coronavirus disease 2019 (COVID-19) has become the most critical health crisis at present, and research is continued about the exact pathophysiology, presentations, and complications of this pandemic. It influences several organs, and many studies have addressed the organs, the involvement of which during the COVID-19 results in patients’ death. One of the important organs that can be involved during COVID-19, which is also a transmission route of the disease, is the eye. According to the evidence, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) can have ocular manifestations and complications. According to the literature, conjunctivitis is the most common presentation, which can develop at any stage of COVID-19 (during and even after the disease), and the major pathophysiology of the eye involvement during the disease is attributed to the direct effect of the virus on the eyes, tissue damage caused by inflammation, underlying diseases, and the adverse effect of the medications prescribed. There are also reports of life-threatening complications, such as rhino-orbital cerebral mucormycosis, which require urgent treatment and are associated with a great mortality rate. Ocular manifestations may also be the presentation of a life-threatening event, such as stroke; therefore, it is necessary to pay great attention to the ocular manifestations during COVID-19. In this review, after about two years of the pandemic started, we present a narrative review on ocular manifestations during COVID-19, categorized into three main categories; ophthalmic, orbital, and neuro-ophthalmological manifestations with a detailed description of the presenting symptoms, risk factor, diagnostic, and therapeutic strategies suggested for each.